Foreign Exchange Exposure of Football Clubs - Nath-Hazarika, Amar (2007)
The Premier League is a billion pound industry and English football clubs can deal with significant amounts of foreign cash flow. This dissertation seeks to investigate if and how English football clubs protect themselves against foreign exchange exposure and how this compares to regular UK MNCs. From examination of the financial reports, some of the football clubs in the Premier League state that they manage foreign exchange risk and use financial instruments to do so, whereas others do not mention foreign exchange risk management. This suggests that either these clubs do not deal in foreign currencies, they do not hedge any foreign exchange exposure or that they do hedge their exposure and do not disclose so in their annual reports. From interviews, I found that the main sources of foreign exchange exposure arise from transfer dealings, prize money from European competition and in some cases tours of foreign countries. The attitudes towards foreign exchange risk vary between clubs and, as one might expect, are dependent on the extent of their activity in the foreign transfer market. The different hedging strategies utilised range from forward contracts to the use of foreign exchange bank accounts, netting and seeking to fix any foreign transfer dealings in sterling. Options do not appear to be used as a hedging technique. Therefore, some English football clubs do use similar foreign exchange risk management strategies as that of UK MNCs and further underlines the fact that football is now as much of a business as it is a sport.